Risco de inundação nas bacias hidrográficas dos rios Henrique e Suzana na área urbana de Erechim, Rio Grande do Sul, Brasil - Furlan, André Ricardo (2019)
In the face of the present environmental crisis, on a global, regional and local scale, uncertainties are created regarding the activities of natural processes in their anthropogenic stage, which affect different social strata of the population. In view of this, the insertion of the themes related to the urbanization process and the formation of risk areas becomes pertinent to understand the stages of the formation of the social fabric, superimposed on the physical-natural components. In this context, the main objective of the research is to identify and analyze the constitution of flood risk areas, focusing on the Suzana and Henrique river basins, located in the urban area of Erechim, State of Rio Grande do Sul. South. To carry out the analysis, we sought to understand the concept of risk and its categories: susceptibility, danger and vulnerability. In addition, we sought to understand the effects of the urbanization process that alter river regimes. The methodological procedures are based on bibliographical research and on stages carried out in the laboratory and in the field. The laboratory analysis carried out in a GIS environment sought to verify the physicalnatural components in order to identify the susceptible and dangerous areas. Field verification corresponds to vulnerability analyzes, where the typology of households is verified, based on the cadastre. In order to arrive at the risk analysis, a cross-check was made between danger and vulnerability. Finally, it was possible with this research to understand, identify and classify different levels of risk ranging from very high, high, medium and low. It was possible to identify 68 households identified in the Henrique river basin and 54 households in the Suzana river basin. In the Henrique river basin, the highest percentages of households fall on the High Risk. It was verified that in the Suzana river basin the highest percentages of households are on High Risk. Therefore, urbanization in these areas did not follow adequate planning, as it exposes the population to risk. Due to the lack of urban planning occurred the occupation of floodplain areas and as well as the construction in floodplain and river terraces, thus providing for the emergence of flood risk areas.